2020
DOI: 10.1002/ppap.202000195
|View full text |Cite
|
Sign up to set email alerts
|

Rational approaches for optimizing chemical functionality of plasma polymers: A case study with ethyl trimethylacetate

Abstract: Improved retention of desirable chemical structures during plasma polymerization requires rational tailoring of plasma‐phase conditions. Using ethyl trimethylacetate, we studied the effects of pressure and power on the contribution of intact molecular ions to deposition and retention of ester groups. The abundance of protonated molecular ions in plasmas varies with pressure and power, but the functionality of plasma polymers, assessed by X‐ray photoelectron spectroscopy and time‐of‐flight secondary ion mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Different strategies to obtain stable and functional PPFs have thus been explored including formation of a vertical gradient structure in the PPF during plasma deposition and chemical post-plasma treatments [195]. Recently, protonation of the starting molecules in the gas phase has been identified as an interesting approach to avoid strong fragmentation of monomers bearing functional groups at moderate SEI [196]. The examination of the fragmentation pathways of ethanol, C 2 H 5 OH, acetic acid, CH 3 COOH, and glucose, C 6 H 12 O 6 , in a plasma by ICP-MS revealed that protonated molecules are indeed more stable in the gas phase than the free molecules [197].…”
Section: Deposition Of Polymer-like Soft Plasma Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different strategies to obtain stable and functional PPFs have thus been explored including formation of a vertical gradient structure in the PPF during plasma deposition and chemical post-plasma treatments [195]. Recently, protonation of the starting molecules in the gas phase has been identified as an interesting approach to avoid strong fragmentation of monomers bearing functional groups at moderate SEI [196]. The examination of the fragmentation pathways of ethanol, C 2 H 5 OH, acetic acid, CH 3 COOH, and glucose, C 6 H 12 O 6 , in a plasma by ICP-MS revealed that protonated molecules are indeed more stable in the gas phase than the free molecules [197].…”
Section: Deposition Of Polymer-like Soft Plasma Coatingsmentioning
confidence: 99%
“…Protonated molecules can thus also be detected by mass spectrometry, that is, at a significant distance from the plasma. The H + -loaded molecular ions are accelerated in the plasma towards the substrate, where soft landing of protonated molecules retains their functionality [196]. This way, plasma polymer coatings were deposited from ethyl αbromoisobutyrate that retained α-bromoisobutyryl functional groups able to graft a dense layer of HEMA polymer brushes to allow for a soft material surface [198].…”
Section: Deposition Of Polymer-like Soft Plasma Coatingsmentioning
confidence: 99%
“…This has been accompanied by much fundamental research on the physicochemical processes in plasma polymerization and their control and fine‐tuning, [ 2,3,11 ] on detailed characterization of the surface chemistries and properties of plasma polymers, [ 12,13 ] and on tailoring the surface chemistries and properties of plasma polymers including optimization of the surface density of specific functional groups such as amines, [ 14 ] carboxylic groups, [ 15–17 ] aldehyde, [ 18,19 ] and ester groups. [ 2,3,20–23 ] Volatile monomers bearing the functional group of interest are utilized (e.g., acrylic acid or oxazoline [ 24 ] to produce COOH groups or aliphatic amines for NH 2 groups), and low monomer fragmentation plasma conditions (e.g., low power, pulsed plasmas at a low duty cycle, reduced ion bombardment at the surface of the substrate, etc. ), for optimal retention of the structure of the monomer and incorporation of the functional group in the resulting coating.…”
Section: Introductionmentioning
confidence: 99%
“…The unique features of plasma polymers have led to extensive research on fundamental questions such as improved control of the bulk and surface chemistries, [2,3] and a wide range of applications-oriented research and development projects towards their utility for specific intended applications. A key premise has been the ability of plasma polymers to form uniform, well-adhering coatings on a wide range of substrate materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation